Emotion Regulation Process for Students Who Perpetrate Self-Injury - Rahmah, Firda Kurnia; Ramdani, Rina Nurhudi; Taufik, Agus; Ilfiandra, Ilfiandra (IAIN Kudus, 2023)
Emotion Regulation Process for Students Who Perpetrate Self-Injury. Self-injury is a form of intentional behavior to harm oneself in order to reduce psychological suffering. While the majority of individuals try to focus on the problems they face, different things happen to those who tend to hurt themselves. Self-injury is related to students' emotional regulation, because a person's emotional response can take him in the wrong direction and the emotions he feels are not appropriate to the situation. Therefore, researchers aim to determine the process of emotional regulation in students who commit self-injury. This research uses a qualitative method with a case study approach. Data were analyzed using data reduction, data presentation and drawing conclusions. The research results show the emotional regulation process in subjects C and F. The emotional regulation process starts with selecting a situation for the subject until the final process is a change in the subject's response to deciding to carry out self-injury and the subject feels satisfied..Keywords: Self Injury, Emotion Regulation, Students